Individuals with Unilateral Transtibial Amputation and Lower Activity Levels Walk More Quickly when Using a Hydraulically Articulating Versus Rigidly Attached Prosthetic Ankle-Foot Device. Issue 3 (July 2018) - Barnett, Cleveland T.; Brown, Olivia H.; Bisele, Maria; Brown, Marcus J.; De Asha, Alan R.; Strutzenberger, Gerda
ABSTRACT: Introduction: Prosthetic ankle-foot devices incorporating a hydraulic articulation between the pylon and prosthetic foot have been shown to be beneficial to the gait of more active individuals with unilateral transtibial amputation (UTA). However, the functional benefits of using hydraulic ankle-foot devices to less active individuals with UTA are yet to be determined. The aim of the current study was to investigate the effects on gait performance of using a non-energy-storage-and-return foot with a hydraulic attachment compared with an identical rigidly attached foot during overground walking in less active individuals with UTA. Materials and Methods: Kinematic and kinetic data were recorded while five individuals with UTA, deemed K2 activity level by their prescribing physician, performed two-minute walk tests (2MWTs) and 10 overground gait trials in two conditions: using a hydraulically articulating ankle-foot device (HYD) and using a rigidly attached ankle-foot device (RIG). Results: Walking speed during the 2MWT was increased by 6.5% on average in the HYD (1.07 m/second) condition compared with the RIG (1.01 m/second) condition (Cohen d = 0.4). Participants displayed more symmetrical interlimb loading ( d = 0.8), increased minimum forward center of pressure velocity ( d = 0.8), increased peak shank rotational velocity ( d = 1.0), and decreased prosthetic energy efficiency ( d = 0.7) when using the HYD compared with the RIG device. Conclusions: Individuals with lower activity levels walk faster and therefore further when using a foot with a hydraulically articulating attachment in comparison with a rigid attachment. A reduced braking effect in early stance phase as a result of the action of the hydraulic component present in the articulating attachment partially explains the improvement in walking performance.